Makna Pengurapan Daud dalam Kepemimpinan Saul berdasarkan Perspektif Pairan Lembä di Mamasa, Sulawesi Barat - Jefri Andri Saputra (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2024)
This article aims to provide an alternative response to the failure of leaders to create prosperity in the life of the church and society. This alternative refers to an analysis of the story of David's anointing and the God's purpose anointed David when Saul was still king in Israel. This research uses a seeing-through approach. The perspective lens for analyzing the story of David's anointing is the lembä pain in Mamasa, West Sulawesi. The author finds that David's anointing strategy aims to maintain the relationship between God and Israel, and God can express His care through David. This strategy implies the urgency of the leadership system's relationship with God and the leader's awareness as a divine agent in bringing prosperity to many people.